An investigation of magma mingling and potential magma mixing during the intrusion of mafic melts into metasediments undergoing partial melting in the Dalradian series of eastern Scotland - Fest, Helena Michaela (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.